2021
DOI: 10.1021/acsomega.1c01388
|View full text |Cite
|
Sign up to set email alerts
|

Dicationic Surfactants as an Additive in Fracturing Fluids to Mitigate Clay Swelling: A Petrophysical and Rock Mechanical Assessment

Abstract: The interactions of clays with freshwater in unconventional tight sandstones can affect the mechanical properties of the rock. The hydraulic fracturing technique is the most successful technique to produce hydrocarbons from unconventional tight sandstone formations. Knowledge of clay minerals and their chemical interactions with fracturing fluids is extremely vital in the optimal design of fracturing fluids. In this study, quaternary ammonium-based dicationic surfactants are proposed as clay swelling inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…The CODcr of sample was determined with potassium dichromate method according to the Chinese national standard, GB/11914-89 [69]. A certain amount of sample was added into a conical flask and oxidized by appropriate amount of potassium bichromate standard solution under the catalysis of sulfuric acid-silver sulfate solution.…”
Section: Ddetermination Of Codcrmentioning
confidence: 99%
See 1 more Smart Citation
“…The CODcr of sample was determined with potassium dichromate method according to the Chinese national standard, GB/11914-89 [69]. A certain amount of sample was added into a conical flask and oxidized by appropriate amount of potassium bichromate standard solution under the catalysis of sulfuric acid-silver sulfate solution.…”
Section: Ddetermination Of Codcrmentioning
confidence: 99%
“…Tariq et al [67][68][69] showed that the use of a solution of cationic gemini surfactants with different spacers resulted in the reduction in the breakdown pressure in unconventional tight sandstones compared to that of the deionized water, which was attributed to the clay stabilization against swelling provided by the surfactant. In addition to the lower breakdown pressure, the use of gemini surfactants allows a reduction in the volume of fluid required to fracture the formation.…”
Section: Oligomeric Surfactantsmentioning
confidence: 99%
“…Tariq et al [ 67 , 68 , 69 ] showed that the use of a solution of cationic gemini surfactants with different spacers resulted in the reduction in the breakdown pressure in unconventional tight sandstones compared to that of the deionized water, which was attributed to the clay stabilization against swelling provided by the surfactant. In addition to the lower breakdown pressure, the use of gemini surfactants allows a reduction in the volume of fluid required to fracture the formation.…”
Section: Oligomeric Surfactantsmentioning
confidence: 99%
“… 22 In the oil field industry, potassium chloride (KCl) is the most commonly used clay stabilizer to prevent wellbore instability caused by swelling in sandstone upon its hydration. 23 The current use of clay stabilizers includes surfactants like quaternary ammonium-based dicationic surfactants 24 and polyoxyethylene quaternary ammonium surfactants; 25 plant extracts like okra mucus extracted from okra plants; 26 , 27 polymers; 28 and nanoparticles. 29 , 30 …”
Section: Introductionmentioning
confidence: 99%
“…The presence of clay minerals in rocks can alter the rock’s mechanical properties when interacting with fresh water . In the oil field industry, potassium chloride (KCl) is the most commonly used clay stabilizer to prevent wellbore instability caused by swelling in sandstone upon its hydration .…”
Section: Introductionmentioning
confidence: 99%